Higher Objectives of Islam in Public Policy and Governance: Analysis from Fethullah Gülen’s Perspective - Recep Dogan (Ar-Raniry: International Journal of Islamic Studies, 2019)
The Qur’ān and Sunnah often justify their rulings that reference the benefits to be achieved from them. Islamic rulings serve to achieve certain objectives and purposes, and it is duty of a Muslim jurist to determine these rulings in consideration of the conditions of his time. Recognizing the rulings in Islam are to achieve certain objectives and purposes contemporary scholar Fethullah Gülen focused on higher objectives of Islam (maqāsid al-shariah) to find solutions of Muslims in his time. In this essay, I tried to analyse higher objectives of Islam in relevance to governance, the state, democracy, public policy and the place of women in family and society. The essay aimed to provide the perspective of Gülen on these issues and analysed his effort in renaissance in the Islamic world.